2015
DOI: 10.1586/17474086.2015.1053456
|View full text |Cite
|
Sign up to set email alerts
|

Bone morbidity in chronic myeloproliferative neoplasms

Abstract: Patients with the classical Philadelphia chromosome-negative chronic myeloproliferative neoplasms including essential thrombocythemia, polycythemia vera and primary myelofibrosis often suffer from comorbidities, in particular, cardiovascular diseases and thrombotic events. Apparently, there is also an increased risk of osteoporotic fractures among these patients. However, the true prevalence, mechanisms involved and therapeutic implications are not well described. In this review, we summarize what is currently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 77 publications
(97 reference statements)
0
6
1
Order By: Relevance
“…A recent Danish registry study has shown that patients with ET and PV have an increased incidence of fractures compared with the general population [ 70 ]. Taking into account that chronic inflammation has been suggested to explain the initiation of clonal development and progression in chronic myeloproliferative neoplasms and other chronic inflammatory diseases that are associated with an increased risk of osteopenia it has been speculated if chronic inflammation might induce osteopenia in MPNs and by this mechanism also predispose to the increased risk of fractures [ 12 , 70 72 ].…”
Section: The Evidence Of Mpns As Inflammatory and Immune Deregulatmentioning
confidence: 99%
“…A recent Danish registry study has shown that patients with ET and PV have an increased incidence of fractures compared with the general population [ 70 ]. Taking into account that chronic inflammation has been suggested to explain the initiation of clonal development and progression in chronic myeloproliferative neoplasms and other chronic inflammatory diseases that are associated with an increased risk of osteopenia it has been speculated if chronic inflammation might induce osteopenia in MPNs and by this mechanism also predispose to the increased risk of fractures [ 12 , 70 72 ].…”
Section: The Evidence Of Mpns As Inflammatory and Immune Deregulatmentioning
confidence: 99%
“…Despite increasing knowledge of the symptom burden in patients with MPN (Abelsson et al, 2013;Christensen et al, 2014;Farmer et al, 2015;Frederiksen et al, 2011;Johansson et al, 2012;Landolfi et al, 2007;Marchioli et al, 2005;Mesa et al, 2007Mesa et al, , 2016Mitra et al, 2013;Scherber et al, 2011Scherber et al, , 2016Wolanskyj et al, 2006), feasibility and effectiveness of an exercise-based rehabilitation intervention have never been explored before in this population (Eckert et al, 2017). In this study, a cohort of patients with MPN took part in a 5day interdisciplinary exercise-based rehabilitation intervention followed by a 12-week self-exercising programme.…”
Section: Discussionmentioning
confidence: 99%
“…In the context, that several studies have established MPN patients with a heavy symptom burden, physical as well as psychological (Abelsson et al, 2013;Christensen et al, 2014;Farmer et al, 2015;Frederiksen et al, 2011;Johansson et al, 2012;Landolfi et al, 2007;Marchioli et al, 2005;Mesa et al, 2007Mesa et al, , 2016Mitra et al, 2013;Scherber et al, 2011Scherber et al, , 2016Wolanskyj et al, 2006), it is obvious to translate this current knowledge-obtained from comprehensive epidemiological studies-into clinical studies exploring preventive measures to help relief the everyday life of patients with MPN. Studies have showed that lowering fatigue and raising QOL have a substantial impact on how long and how (good) people live (Johansson et al, 2012;Mesa et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previously developed mouse model of myeloproliferative neoplasm (MPN) overexpressing thrombopoietin showed that increased expression of OPG was responsible for osteosclerotic manifestations and suggested that OPG was produced by megakaryocytes and platelets. 9,10 Knowing that MPN can be associated with ECD 7 and that osteosclerosis may also occur in patients with MPN, 11 we could assume that osteosclerosis might share common pathogenesis in both diseases. In Langerhans cell histiocytosis (LCH), often associated with ECD, 1,12 increased levels of OPG have been described in three different studies.…”
Section: Erdheim-chester Disease Long-bone Osteosclerosis Can Be Repr...mentioning
confidence: 99%